Antecedents and Consequences of Grit Among Working Adults: A Transpersonal Psychology Perspective - Agrawal, Devanshi; Chukkali, Surekha; Singh, Sabah (Frontiers in Psychology, 2022)
Positive psychology has paved the way for newer and more informed ideas of living a meaningful, integrated and well-rounded quality of living. The current era of the pandemic has also moulded the ways in which individuals perceive their quality of life and how they want to integrate a holistic approach towards their well-being. The workplace settings have seen tremendous changes in terms of how employers, employees and the organisations at large function and operate. The pre-pandemic concept of success has shifted its focus from hard work to developing grit among employees to increase the overall efficiency of the organisations. Grit has revolutionised the conventional standards of success, meaning in life and has impacted personal as well as occupational welfare. This integration of positive psychology and transpersonal psychology has catalysed the purpose for the current study. To help organisations and individuals thrive in their professional endeavours at the workplace and to provide them with relevant psychological tools to enhance their occupational growth, the present study has been conducted empirically to investigate the antecedents and consequences of grit among 209 working professionals in India. The results of this study indicate that the transpersonal capital of metacognition, flow, optimism and empathy have a significant role to play in developing grit among the participants. The findings have implications for enhancing job satisfaction and job performance of participants. The current research also provides a framework to organisations towards designing interventions for improving efficiency at the workplace.